TAHAPAN PELAKSANAAN SISTEM INTELIJEN BISNIS DALAM PERUSAHAAN - Naswirman, Naswirman (JURNAL LENTERA ICT, 2014)
The study focuses on some important things, namely to know the steps that must be implemented in building the Business Intelligence System is good and right on target, examine the right approach in building a Business Intelligence System in an organization, and understand the important aspects that must be considered in order Business Intelligence Systems development investment in the future successfully. The Business Intelligence System Development should be based on conditions and the real needs of the organization in achieving the desired performance level. If this condition occurs, then the decision-making process will be better and more accurate. The purpose of this study to determine the important aspects that must be understood and prepared to implement a Business Intelligence System in an organization. The method used is the explanation as well as the research library of several books, articles and other literature. Key Words: Bussiness Inteligent System, Strategy, Key Performance Index